Pharmacokinetic properties of pravastatin in Mexicans: An open-label study in healthy adult volunteers - Escobar, Yesenia (Elsevier, 2005)
BACKGROUND: The pharmacokinetic properties of pravastatin, particularlyAUC and C(max), are variable by population. A description of the pharmacokinetic properties of pravastatin in Mexican mestizos was not found in a search of MEDLINE/PubMed (key terms: pravastatin, Mexican, and pharmacokinetics; years: 1966–2005). Because Mexicans and Japanese have common ancestors (Mongoloid group), they also have a common gene pool. This gene pool was modified by genetic “bottlenecks” that occurred when these populations migrated to the Americas and when the Mexican population mixed with the Spanish population during the 16th and 17th centuries. Previous studies in Japanese subjects showed 5 main mutations on the hepatic drug transporter OATP-C, resulting in higher C(max) and AUC values compared with whites. In the Japanese population, the rates of expression of the (*)1b and (*)15 alleles were 46% and 15%, respectively. OBJECTIVE: The aim of this study was to evaluate the pharmacokinetic propertiesof pravastatin in healthy Mexican mestizo volunteers and to compare them with those in white and Japanese populations described in the literature. METHODS: This open-label, uncontrolled pilot study of the pharmacokineticproperties of pravastatin was conducted at the Division of Pharmacology, Center for Research and Advanced Studies, Mexico City, Mexico. Healthy, adult, Mexican volunteers received a single dose of pravastatin 10 mg PO (tablet). High-performance liquid chromatography was used to determine plasma pravastatin concentrations between 15 minutes and 12 hours after dosing. RESULTS: Twenty-four subjects (15 women, 9 men; mean age, 30.6 years)participated in the study. The mean (SD) C(max) was 9.5 (2.4) ng/mL; T(max), 0.8 (0.3) hours; AUC(0−∞) 35.7 (19.7) ng/mL - h; t(1/2), 2.7 (1.1) hours; and mean residence time, 3.1 (1.1) hours. One volunteer (4%) had an AUC value that differed substantially from the rest of the study population, producing a bimodal distribution of the pharmacokinetic parameters. No adverse events were observed or reported during the trial. CONCLUSIONS: In this small pilot study of the pharmacokinetic properties of pravastatin in Mexican mestizos, AUC was not statistically significantly different from previous studies, either in a white or Japanese population. However, we did not find the high values reported for C(max) in some Japanese subjects carrying recently reported mutations on the pravastatin transporter.